The Influence of Self-Concept on Feelings of Insecurity Among Students Using Social Media: Study of Instagram and TikTok - marisha, Fara Marisha; Kukuh Setyo Pambudi; Basma Tania; Alya Zulfani Nugroho (Yayasan Ilomata, 2025)
In this modern era, there are more and more social media users. Instagram and TikTok are social media that are widely used by various age groups, from children to adults. Feelings of insecurity can arise as an influence of social media, because from social media we can see people who are more than us. Feelings of insecurity are feelings of insecurity, inadequacy, feelings of always lacking within oneself. Therefore, it is necessary to have a positive or high self-concept, self-concept is an individual's way of viewing himself, self-knowledge, self-assessment and what the individual wants. The aim of this research is to see the influence of self-concept on insecurity in male students who use Instagram and Tiktok. The method used in this research is a quantitative causality approach, the sampling technique used is purposive sampling with the criteria being male college students, aged 18-25 years, Instagram and Tiktok users. A questionnaire containing self-concept and insecurity scales was distributed online via WhatsApp, Instagram and Twitter. After data collection, a simple linear regression hypothesis test was carried out, obtaining a significance value of 0.00 <0.05, so it can be concluded that there is an influence between self-concept and insecurity in male college students who use Instagram and Tiktok.